Joint optimization of NOMA‐enabled backscatter communications for beyond 5G IoT networks. Issue 2 (21st January 2021) - Khan, Wali Ullah; Imtiaz, Nouman; Ullah, Inam
Abstract : This article optimizes the link‐level of NOMA‐enable backscatter communication (BackCom) for beyond fifth‐generation (B5G) Internet‐of‐things (IoT) networks. Specifically, we jointly optimize the transmit‐power (TP) of IoT users and the reflection‐coefficient (RC) of the backscatter tag (BackTag), where the target is to increase the sum capacity (SumCap) of NOMA‐enabled BackCom. The problem of TP and RC is formulated as convex optimization, and we exploit KKT conditions to obtain the optimal solutions. The pure NOMA without BackCom and conventional orthogonal multiple access (OMA) schemes are also presented as the benchmark schemes. Our results significantly outperform the pure NOMA and conventional OMA schemes. Abstract : This letter investigated a joint optimization problem of NOMA‐enabled backscatter communication in beyond 5G IoT networks. The main objective is to maximize the sum‐rate of the system through optimal power allocation at source and efficient reflection coefficient at backscatter tag